ANALISIS RANTAI NILAI UNTUK EFISIENSI DAN PENINGKATAN MARJIN PADA PERUSAHAAN PRODUSEN MUTIARA DI MALUKU - John Papilaja (Soso-Q : Jurnal Manajemen, 2017)
The study was conducted with a view to determining the value chain activities of the smallest on the contract costs and operating costs, such that the company's profit margin in the pearl industry in the province of Maluku became larger above the industry average.By using the analysis of the concept of value chain or value chain in the primary activity and the activity of middle-class pearl cultivation companies analyzed the level of the industry value chain activities in Maluku province through the analysis of the concept of value chains (value chains). Costs associated with the primary activities and support activities are divided into two types of contract costs and operating costs.Population of middle-class pearl cultivation companies in the province of Maluku that as many as 9 units wholly used as the study sample (sample saturated) so that the contract revenue, contract costs, gross profit, operating expenses, operating profit can be determined.The results showed that the efficiency cost of the contract by 9:01% lead to gross operating profit margin increased from 79% to 88.01%. Furthermore, operating expenses decreased by 2.0% causing the operating profit margin industry average increase of 52% to 54%. Keywords: Company of the middle class cultured pearls, pearl industry, contract costs, operating costs, operating gross margin, operating profit margin